Chemical constituents from the thorns of Gleditsia sinensis and their cytotoxic activities. Issue 12 (1st December 2020) - Zhang, Yu-Bo; Lam, Kar-Ho; Chen, Li-Feng; Wan, Hei; Wang, Guo-Cai; Lee, Kai-Fai; Yip, Chun-Wang; Liu, Kwun-Hung; Leung, Pak-Heng; Chan, Hai-Yong; Shi, Yi-Gang; Zhao, Jia; et al.
Abstract: A new aromatic glycoside (1 ) and a new natural product, neolignan (2 ), along with twenty-three known compounds (3-25 ), were isolated from the thorns of Gleditsia sinensis . According to the spectroscopic analyses (IR, UV, HRESIMS, NMR and ECD), the structures of isolates were elucidated. Herein, compounds 4, 6-8, 10-13, 15, 16, 18, 20, 23 were isolated from the plant of G. sinensis for the first time. Moreover, compounds 4, 6, 15 and 24 showed cytotoxic effects on human ovarian cancer (SKOV-3) cells with IC50 values of 24.83 ± 4.90, 48.86 ± 9.11, 80.13 ± 5.62, 15.38 ± 2.21 μM, respectively.